2004
DOI: 10.1159/000081971
|View full text |Cite
|
Sign up to set email alerts
|

Fish Protein Stimulated the Fibrinolysis in Rats

Abstract: Objective: We hypothesized that fish protein affects blood coagulation and/or fibrinolysis, and compared the activity and amounts of factors involved in blood coagulation and fibrinolysis in rats fed the fish protein, which was treated to remove water-soluble and ethanol-soluble elements, from sardine (sardine protein). Methods: In the first experiment, rats were fed for 21 days an AIN-93G-based control diet, and diets in which the casein of the control diet was exchanged for sardine protein at 5, 10 and 20% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…It is known that DHA is effective for prevention and improvement of cerebrovascular disorders, dementia, ischemic heart disease, high blood pressure, arteriosclerosis, chronic inflammation, hyperlipidemia, and dermatitis by decreasing arachidonic acid in plasma and internal organs [22][23][24][25] . The beneficial effects to health and amelioration of cardiovascular and cerebrovascular diseases due to fish are caused by a combination of the suppressing effect on blood coagulation of n-3 PUFA and the promoting effect on fibrinolysis of fish protein 26) . However, it has been reported that DHA supplementation increased oxidative damage in bone marrow DNA 27) .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that DHA is effective for prevention and improvement of cerebrovascular disorders, dementia, ischemic heart disease, high blood pressure, arteriosclerosis, chronic inflammation, hyperlipidemia, and dermatitis by decreasing arachidonic acid in plasma and internal organs [22][23][24][25] . The beneficial effects to health and amelioration of cardiovascular and cerebrovascular diseases due to fish are caused by a combination of the suppressing effect on blood coagulation of n-3 PUFA and the promoting effect on fibrinolysis of fish protein 26) . However, it has been reported that DHA supplementation increased oxidative damage in bone marrow DNA 27) .…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoded for Plg and tPA were identified in the blowfish Fugu rubripes (Jiang and Doolittle 2003). Rats with diets based on fish oil decrease the fibrinolytic activity due to an increase of PAI-1 (Sano et al 2003), whereas dietary supplementation with fish protein increases fibrinolysis by increasing tPA in blood (Murata et al 2004). …”
Section: Fibrinolytic Parametersmentioning
confidence: 99%
“…A series of studies found that soy protein [1][2][3][4] and fish protein [5] are capable of lowering blood lipid levels when compared with casein as a control protein. Moreover, it has been reported in a few studies that soy protein is capable of altering the transcription levels of hepatic sterol regulatory element-binding proteins (SREBPs) which in turn leads to the observed lipidlowering effect [2,4,6] .…”
Section: Introductionmentioning
confidence: 99%